Optoelectronics Materials and Techniques - Predeep, Padmanabhan (IntechOpen, 2011)
Optoelectronics - Materials and Techniques is the first part of an edited anthology on the multifaceted areas of optoelectronics by a selected group of authors including promising novices to the experts in the field. Photonics and optoelectronics are making an impact multiple times the semiconductor revolution made on the quality of our life. In telecommunication, entertainment devices, computational techniques, clean energy harvesting, medical instrumentation, materials and device characterization and scores of other areas of R&D the science of optics and electronics get coupled by fine technology advances to make incredibly large strides. The technology of light has advanced to a stage where disciplines sans boundaries are finding it indispensable. Smart materials and devices are fast emerging and being tested and applications developed in an unimaginable pace and speed. Here has been made an attempt to capture some of the materials and techniques and underlying physical and technical phenomena that make such developments possible through some real time players in the field contributing their work and this is sure to make this collection of essays extremely useful to students and other stake holders such as researchers and materials scientists in the area of optoelectronics.